2015
DOI: 10.1016/j.iref.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Investor response to public news, sentiment and institutional trading in emerging markets: A review

Abstract: This paper reviews the literature on investor reaction and sentiment with respect to public information arrival in emerging markets and discusses the implications of the findings for the validity of theoretical models emphasizing public information arrival as the main mover of asset prices. We cover three types of public information news: monetary policy announcements, the International Monetary Fund (IMF) related news and other public and political news. In addition, we review the literature on sentiment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 123 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…Brzeszczyński, Gajdka and Kutan (2015) There is ample empirical evidence that devoted to the investors' sentiment and equity returns nexus without reaching a uniform consensus 4 . The major advantage of the wavelet methodology is that it can distinguish between short-term and long-term co-movement dynamics between sentiment and equity returns.…”
Section: Introductionmentioning
confidence: 99%
“…Brzeszczyński, Gajdka and Kutan (2015) There is ample empirical evidence that devoted to the investors' sentiment and equity returns nexus without reaching a uniform consensus 4 . The major advantage of the wavelet methodology is that it can distinguish between short-term and long-term co-movement dynamics between sentiment and equity returns.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that this effect is stronger for difficult-to-arbitrage firms-that is, small, young, highly volatile, or unprofitable firms. Baker, Wurgler, and Yuan (2012) [53] expanded this analysis to a global sample and found similar results, and Brzeszczynski, Gajdka, and Kutan (2015) [54], Chen and Lien (2017) [55], and Seok, Cho, and Ryu (2019a) [22] investigated the relationship between sentiment and news and found that investors react more strongly to good news when sentiment is high.…”
Section: Literature Reviewmentioning
confidence: 72%
“…Every research has absolutely limitation, it is the same in this study. It seems that it does not review from political and economic side in reviewing investors psychology, in fact it is known to have close correlation [25], it remembers that study of investors psychlogy is very important relating to company's share value.…”
Section: Resultsmentioning
confidence: 99%
“…Almost of investors reveal that financial information presented by company becomes the important consideration in investment decision making process [24]. Although investors behaviour of a company has differentiation, it is especially investors behaviour has state differences because of the existence of cultural differences [25]. Like stated by Chang & Lin [4] who emphasizes that "investor behaviour is dominated by national cultural differences, recent literature on national cultural investigations is needed for empirical analysis".…”
Section: Investor Psychologymentioning
confidence: 99%